Cryostratigraphy and Permafrost Evolution in the Lacustrine Lowlands of West‐Central Alaska. (12th February 2014) - Kanevskiy, Mikhail; Jorgenson, Torre; Shur, Yuri; O'Donnell, Jonathan A.; Harden, Jennifer W.; Zhuang, Qianlai; Fortier, Daniel
ABSTRACT The influence of permafrost growth and thaw on the evolution of ice‐rich lowland terrain in the Koyukuk‐Innoko region of interior Alaska is fundamental but poorly understood. To elucidate this influence, the cryostratigraphy and properties of perennially frozen sediments from three areas in this region are described and interpreted in terms of permafrost history. The upper part of the late Quaternary sediments at the Koyukuk and Innoko Flats comprise frozen organic soils up to 4.5 m thick underlain by ice‐rich silt characterised by layered and reticulate cryostructures. The volume of visible segregated ice in silt locally reaches 50 per cent, with ice lenses up to 10 cm thick. A conceptual model of terrain evolution from the Late Pleistocene to the present day identifies four stages of yedoma degradation and five stages of subsequent permafrost aggradation‐degradation: (1) partial thawing of the upper ice wedges and the formation of small shallow ponds in the troughs above the wedges; (2) formation of shallow thermokarst lakes above the polygons; (3) deepening of thermokarst lakes and yedoma degradation beneath the lakes; (4) complete thawing of yedoma beneath the lakes; (5) lake drainage; (6) peat accumulation; (7) permafrost aggradation in drained lake basins; (8) formation of permafrost plateaus; and (9) formation and expansion of a new generation of thermokarst features. These stages can occur in differing places and times, creating a highly complex mosaic of terrain conditions, complicating predictions of landscape response to future climatic changes or human impact. Copyright © 2014 John Wiley & Sons, Ltd.